2014
DOI: 10.1186/ar4447
|View full text |Cite
|
Sign up to set email alerts
|

Adiposity and hand osteoarthritis: the Netherlands Epidemiology of Obesity study

Abstract: IntroductionObesity, usually characterized by the body mass index (BMI), is a risk factor for hand osteoarthritis (OA). We investigated whether adipose tissue and abdominal fat distribution are associated with hand OA.MethodsThe Netherlands Epidemiology of Obesity (NEO) study is a population-based cohort aged 45 to 65 years, including 5315 participants (53% women, median BMI 29.9 kg/m2). Fat percentage and fat mass (FM) (kg) were estimated using bioelectrical impedance analysis. The waist-to-hip ratio (WHR) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
73
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(81 citation statements)
references
References 67 publications
6
73
0
2
Order By: Relevance
“…Some studies [45,46,49,64,66▪,97▪,102] have highlighted interactions among these risk factors (mostly surrounding sex differences in other osteoarthritis risk factors); given the multifactorial nature of osteoarthritis, future research should carefully consider these interrelationships. Also important is the existence of multiple known modifiable or preventable risk factors for osteoarthritis incidence and/or progression (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies [45,46,49,64,66▪,97▪,102] have highlighted interactions among these risk factors (mostly surrounding sex differences in other osteoarthritis risk factors); given the multifactorial nature of osteoarthritis, future research should carefully consider these interrelationships. Also important is the existence of multiple known modifiable or preventable risk factors for osteoarthritis incidence and/or progression (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…A Netherlands-based cohort study [45] found that percentage body fat, fat mass, and waist-to-hip ratio were all associated with hand osteoarthritis; visceral adipose tissue was associated with hand osteoarthritis in men only. The association of obesity with hip osteoarthritis has been weak and inconsistent across studies [11,12].…”
Section: Person-level Risk Factorsmentioning
confidence: 99%
“…Almost half of the association between elevated BMI and knee OA was explained by serum leptin level in the Maintenance of Balance, Independent Living, Intellect, and Zest in the Elderly Boston Study (22). In the Netherlands Epidemiology of Obesity study, knee OA was associated with weight and fat-free mass, adjusting for metabolic factors, and hand OA was associated with the metabolic syndrome, adjusting for weight (23). In a study of patients undergoing total knee or hip replacement due to primary OA in Newfoundland, Canada, metabolomics analysis of synovial fluid samples demonstrated metabolically distinct subgroups (24).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to knee OA, increased BMI is also associated with OA of the hips 7 and the hands 8, 9 . Data from the Netherlands Epidemiology of Obesity (NEO) study show that BMI and fat mass were associated with both knee 10 and hand OA 9 . The association of BMI and fat mass with hand OA in particular suggests that inflammatory and metabolic factors, rather than simply excessive joint loading, may be contributing to the higher risk of development of OA with obesity.…”
Section: Introductionmentioning
confidence: 99%